FREQUENCY OF COMPLETE HEART BLOCK AFTER SURGICAL CLOSURE OF PERIMEMBRANOUS VENTRICULAR SEPTAL DEFECT - Shah, Syed Murad Ali; Ullah, Ikram; Khan, Muhammad Gibran; Ullah, Naseem; Malik, Abdul; Khan, Riaz Anwar (Journal of Postgraduate Medical Institute, 2016)
Objective: To find the frequency of complete heart block (CHB) in patients undergoing surgical perimembranous Ventricular septal defect (VSD) closure. Methodology: This was a Descriptive cross sectional study performed in Car -diovascular Department Lady Reading Hospital Peshawar. Data was collect-ed from 28 January 2013 to 28 July 2013 with sample size of 103.Sampling technique was non probability consecutive. All patients with perimembranous ventricular septal defect, aged 5 years to 25 years with any gender were in-cluded in the study. Results:-Mean age was 12.63 years ± 6.63. Patients were divided in four cat -egories according to their age. Over all complete heart block in the perimem-branous ventricular septal defect after surgical closure was 10(9.71%). Age wise distribution of complete heart block shows that majority of the complete heart block 6(12.8%) were found in age less than or equal to 10 years. Conclusion:-VSD closure is less often associated with CHB but there should be arrangements for pace maker to timely pace the patient in case of any emergency.